Development of Watershed of River Valley Projects through Soil Conservation Measures - Shettar, M.G. (Journal of Soil and Water Conservation, 2022)
Land and water are the most important natural resources gifted to man by Nature. Though these resources are exhaustible, yet not only they are replanishable but also they can be developed, to meet the increasing demands of the developing economy of the developing Countries. The success of the programme of the development of land and water resources depends on how best the programme is thought out and how effectively it is executed, keeping in view the cost inolved in the execution of the measures proposed and the benefits expected to accrue out of them. In this short note an effort is made to bring out some of the principles according to which the watershed as a unit should be treated under various soil conservation mea-sures to have an effect control over the soil loss due to surface run off, which subsequent-ly finds its way through the running streams and nallas to the River Valley Projects and gets deposited in them and thus reduces the useful life of the Projects.